Teaching of psychology and pedagogics at the basic faculties of the Peoples' Friendship University of Russia - A V Gagarin (Peoples' Friendship University of Russia (RUDN University), 2009)
In this Article are presented history, a current state and prospects of development of system of teaching of psychology and pedagogics at not psychological faculties and branches of the Russian university of friendship of the people.